Analysis of cortisol in dog hair - a potential biomarker of chronic stress: a review - L. Mesarcova; J. Kottferova; L. Skurkova; L. Leskova; N. Kmecova (Veterinární Medicína, 2017)
Cortisol, which is produced in the adrenal glands, is an endogenous glucocorticoid hormone that delivers its hormonal message to cells by acting on glucocorticoid receptors. It is one of the main stress hormones responsible for stress responses in animals and humans, and its overproduction is characteristic of certain diseases. While acute stress disorder can be evaluated by means of measuring the cortisol concentration in blood and urine, chronic stress disorder can be detected by monitoring the cortisol concentration in fur or hair. Hair collection is simple, inexpensive and non-invasive, and can be performed easily and rapidly; thus, it appears to be a suitable method for determining the level of stress in dogs from shelters, abused dogs or dogs involved in different types of animal interactions. Since it is a relatively new method, monitoring cortisol in hair or fur requires further research in order to definitively prove its efficacy, and possibly to determine reference range values for different breeds of dogs.